2014
DOI: 10.1155/2014/607192
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Comorbidities in Adult Severe Asthmatics

Abstract: Both severe asthma and obesity are growing health problems. Severe asthma leads to a poor quality of life. The relationship among BMI, comorbidities, and severe asthma control in adults is still unclear. The aim of the study is to better understand the effect of the comorbidities as atopy, type II diabetes, OSAS, gastroesophageal reflux, hypertension, cardiovascular diseases, osteoporosis, infections, and psychological factors with BMI on asthma control in a cohort of adult severe asthmatics. One hundred and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 32 publications
0
40
0
2
Order By: Relevance
“…The mechanical effect of obesity is of little meaning. Concomitant diseases such as esophageal reflux disease, sleep apnea, and diabetes were more important [7]. The significant increase in the number of exacerbations in this group confirms that obesity exerts a negative influence on the course of asthma.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The mechanical effect of obesity is of little meaning. Concomitant diseases such as esophageal reflux disease, sleep apnea, and diabetes were more important [7]. The significant increase in the number of exacerbations in this group confirms that obesity exerts a negative influence on the course of asthma.…”
Section: Discussionmentioning
confidence: 57%
“…Obesity mechanically impairs breathing, leading to mild restriction, and moderates the immune system, which results in systemic inflammation [5,6]. In obese people sleep apnea and esophageal reflux are more common [7]. The comparison of two populations of patients suffering from asthma: obese and of normal weight, revealed that in the first group there are more women, the quality of life is lower, asthma exacerbations are more frequent, and the response to inhaled corticosteroids is poorer, which results in a higher demand for corticosteroids [8].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the data clearly supports the link between obesity and asthma, and obese and overweight patients have a difficulty in being treated due to reduced efficacy of the treatment(s), and their symptoms are exacerbated by a coexisting obesity 37,38 . Therefore, weight loss in these patients with asthma and obesity may not only lead to the improvements in asthma control, but also improve the response to medications, and overall asthma-related quality of life.…”
Section: Obesity and Asthma Managementmentioning
confidence: 63%
“…The data from a recent study showed that the anthropometric obesity measures correlated with a poor efficacy and poor quality of life and life in obese patients with asthma 34,35 , and increased the risk of hospitalizations 36 . Overall, the data clearly supports the link between obesity and asthma, and obese and overweight patients have a difficulty in being treated due to reduced efficacy of the treatment(s), and their symptoms are exacerbated by a coexisting obesity 37,38 . Therefore, weight loss in these patients with asthma and obesity may not only lead to the improvements in asthma control, but also improve the response to medications, and overall asthma-related quality of life.…”
mentioning
confidence: 63%